Tren Riset Global Obat Herbal dalam Kesehatan Reproduksi Wanita: Analisis Bibliometrik 10 Tahun dari Database Scopus (2016–2026) - Saddam Muhdi; Frida Septiani Tavia; Faishal Alfayyedh (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Female reproductive disorders are increasingly rising globally, triggering an escalation in complementary research based on natural products. This study aims to map research trends, publication volume, geopolitical dominance, collaboration circles, and conceptual clusters regarding herbal medicine in women's reproductive health over the past decade. A descriptive and longitudinal bibliometric analysis was conducted using secondary data extracted from the Scopus database across the 2016–2026 period. Data were analyzed quantitatively and visually using Biblioshiny (R-Bibliometrix) and VOSviewer software through performance evaluation and science mapping techniques. Annual scientific production demonstrates a consistent growth trend. Frontiers in Pharmacology serves as the most relevant outlet with the highest manuscript volume, while BMC Complementary and Alternative Medicine recorded the largest local citation impact (H-index = 17). China absolutely dominates the global landscape (3,723 citations) and forms a close co-authorship alliance axis with South Korea and the United States. Keyword co-occurrence mapping reveals major clinical factions centered on the management of polycystic ovary syndrome (PCOS), endometriosis, and reproductive aging (menopause), universally linked by oxidative stress mitigation pathways. Recent trends (2024–2026) detect a surge in bioinformatics research (molecular docking) and specific testing on human granulosa cell lines (KGN cell line). Research over the past decade demonstrates a paradigm shift from macro empirical treatment toward integrative reproductive medicine at the sub-cellular level. This study provides a strategic navigation map for academics to identify translational research gaps and formulate formal clinical practice guidelines in the future.